Missouri caves in history and legend - Weaver, H. Dwight (Missouri heritage readers., 2008)
"Examines the historical and cultural significance of Missouri caves, describing ways that people have used them historically for shelter, cold storage, burials, moonshine stills, mining, and even as hideouts for Civil War soldiers and outlaws including Jesse James. Describes growing public appreciation and conservation of these unique and beautiful resources"--Provided by publisher.